Powder mixed micro electro discharge milling of titanium alloy: Investigation of material removal rate - Ali, Mohammad Yeakub; Abdul Rahman, Nur Atiqah; Mohamad Aris, Erniyati (2011)
This paper presents effects of silicon carbide (SiC) powder in dielectric fluid of micro EDM on material removal rate (MRR). The aim is to identify the optimum level of SiC powder concentration and other micro EDM parameter for higher MRR. The work material was titanium alloy (Ti-6Al-4V) machined with tungsten carbide (WC) electrode by varying two machining parameters SiC powder concentrations and discharge energy. By using two factor four level factorial design of experiment, sixteen experiments were conducted. Data were analyzed by Design Expert® software. In this experimental investigation, maximum MRR of 7.3 µg/min was obtained for 24.75 g/l SiC powder concentration and 56.77 µJ discharge energy. The analysis of variance revealed that the SiC powder concentration in dielectric fluid on micro EDM has significant influence on MRR Ti-6Al-4V titanium alloy.